Optimizing Quizizz for EFL interactive student worksheet in Merdeka Curriculum - Rachman, Arif (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
Recently, Merdeka Curriculum has started to be implemented in all elementary to high schools in Indonesia. One of the principles of Merdeka Curriculum is the students' profile (i.e. visual, auditory and kinesthetic). One of the strategies which can be applied by EFL teachers in promoting the principle is by utilizing Quizizz as EFL Interactive Student Worksheet. This study intends to investigate the students' perception regarding the use of Quizizz to promote the interactive worksheet. This study is a kind of Class Action Research. It involved 150 students as the participants, and used both questionnaires and semi-structured interviews to collect the data. The data were analyzed using a descriptive qualitative method in this study. The findings of the study revealed that students are very excited in accomplishing the interactive worksheet because they can be provided by delightful materials including several interesting and interactive activities such multiple choice, filling the blank, listening, drawing, and poÄºling in one whole activity. In addition, they believe that the worksheet in the quizizz is effective to motivate them in learning English. Thus, teachers can optimize many kinds of Quizizz features to make the EFL teaching and learning process more delightful, interactive and effective to meet the principle of Merdeka Curriculum.